2019
DOI: 10.1186/s12885-019-5655-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between TIMP-2 gene polymorphism and breast cancer in Han Chinese women

Abstract: Background TIMP-2 gene plays an important role in the development of breast cancer. The present study was conducted to evaluate whether TIMP-2 gene polymorphisms are associated with breast cancer risk in a Han Chinese cohort. Methods Six single nucleotide polymorphisms (SNPs) within the TIMP-2 gene in 571 breast cancer and 578 healthy control subjects were genotyped through the Agena MassARRAY. Logistic regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…A total of 19 candidate SNPs were analyzed in this study, including rs5757573, rs2285094 in PDGFB , rs2228230, rs1800812 in PDGFRA , rs2302273, rs246395 in PDGFRB , rs1449683, rs1048201 in FGF , rs2981582 in FGFR2 , rs243865, rs7201 in MMP2 , rs17576, rs17577 in MMP9 , rs4898, rs2070584 in TIMP1 , rs2277698, rs7501477 in TIMP2 , and rs9862, rs9619311 in TIMP3 ( Table S2 ). These were SNPs that had a minor allele frequency (MAF) ≥10% in the European Caucasian population [ 23 ] and functional significance, and/or were located in coding or regulatory regions, and/or were reported as associated with cancer risk or outcome for other solid cancers [ 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Genomic DNA was isolated from frozen peripheral blood with Genomic Maxi AX kit (A&A Biotechnology, Gdynia, Poland).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 19 candidate SNPs were analyzed in this study, including rs5757573, rs2285094 in PDGFB , rs2228230, rs1800812 in PDGFRA , rs2302273, rs246395 in PDGFRB , rs1449683, rs1048201 in FGF , rs2981582 in FGFR2 , rs243865, rs7201 in MMP2 , rs17576, rs17577 in MMP9 , rs4898, rs2070584 in TIMP1 , rs2277698, rs7501477 in TIMP2 , and rs9862, rs9619311 in TIMP3 ( Table S2 ). These were SNPs that had a minor allele frequency (MAF) ≥10% in the European Caucasian population [ 23 ] and functional significance, and/or were located in coding or regulatory regions, and/or were reported as associated with cancer risk or outcome for other solid cancers [ 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Genomic DNA was isolated from frozen peripheral blood with Genomic Maxi AX kit (A&A Biotechnology, Gdynia, Poland).…”
Section: Methodsmentioning
confidence: 99%
“…TIMP2 has been reported to interact with multiple membrane receptors, such as integrin α3β15, insulin-like growth factor 1 receptor (IGFR1) and membrane-bound MMP1, 4, 6 (10)(11)(12), which play a role in homeostasis regulation at the interface with ECM. Imbalanced TIMP2 expression has been found to be associated with different types of cancer and metastasis, and in several cases it has been shown to be associated with poor patient outcomes (13), such as breast cancer (14), ovarian cancer (15) and gastric cancer(16).…”
Section: Introductionmentioning
confidence: 99%
“…Different data were obtained in Wang et al, study, which showed the highest percentage of staging was at the localized stage (stages I, and II). 16 This may be due to the high awareness of women in that population through early detection of breast cancer such as mammography test, so that the prevalence can be suppressed. 17,18 Early detection of breast cancer can be done when someone knows the factors related to the risk of suffering from breast cancer.…”
Section: Resultsmentioning
confidence: 99%